Cost-effectiveness of atezolizumab versus chemotherapy in patients with non-small-cell lung cancer ineligible for platinum-based doublet chemotherapy - Wu, Qiuji; Qin, Yi; Li, Qiu (Frontiers in Public Health, 2025)
BackgroundAtezolizumab has recently demonstrated improved prognosis in patients with advanced or metastatic non-small-cell lung cancer (NSCLC) who are not eligible for treatment with a platinum-containing regimen, as observed in a randomized phase 3 clinical trial. This study aims to evaluate the cost-effectiveness of atezolizumab for the treatment of NSCLC from the perspective of payers in both developed and developing countries.Materials and methodsA Markov model was developed to simulate treatment scenarios involving atezolizumab or chemotherapy for patients diagnosed with NSCLC. The model estimated the transition probabilities, health care costs, and health utilities base on the risk of disease progression, survival, and toxicity using data from IPSOS clinical trials, relevant literature, and publicly available databases. A price simulation was conducted to guide the pricing strategy at the specified willingness-to-pay (WTP) threshold, and sensitivity analyses were performed to assess the model’s response to uncertainty.ResultsAmong patients with NSCLC who are not suitable for treatment with a platinum-containing regimen, the use of atezolizumab led to an incremental gain of 0.35 quality adjusted life years (QALYs) compared to chemotherapy. The ICER for atezolizumab compared to chemotherapy was calculated at 220400.53 per QALY in the US and 101874.61 per QALY in China. The price simulation results indicated that atezolizumab was favored in the US when the price was less than 371.28/60 mg and 474.92/60 mg at the WTP thresholds of 100,000 and 150,000, respectively; it was cost-effective at a WTP threshold of 36023.71when the price was about 40% of the current price in China. Sensitivity analysis revealed that variables such as the price of atezolizumab and utilities influenced the r model’s outcomes, although these factors did not significantly alter the overall conclusion.ConclusionAtezolizumab was not considered cost-effective at the WTP thresholds of 150,000 per QALY in the US and 36,024 per QALY in China for patients with advanced NSCLC who are ineligible for platinum-based chemotherapy.